Anthropometric models to estimate fat mass at 3 days, 15 and 54 weeks. Issue 3 (24th September 2021) - Gopalakrishnamoorthy, Mahalakshmi; Whyte, Kathryn; Horowitz, Michelle; Widen, Elizabeth; Toro‐Ramos, Tatiana; Johnson, Jill; Gidwani, Sonia; Paley, Charles; Rosenn, Barak; Lin, Susan; Thornton, John; Pi‐Sunyer, Xavier; et al.
Summary: Background: Currently available infant body composition measurement methods are impractical for routine clinical use. The study developed anthropometric equations (AEs) to estimate fat mass (FM, kg) during the first year using air displacement plethysmography (PEA POD® Infant Body Composition System) and Infant quantitative magnetic resonance (Infant‐QMR) as criterion methods. Methods: Multi‐ethnic full‐term infants ( n = 191) were measured at 3 days, 15 and 54 weeks. Sex, race/ethnicity, gestational age, age (days), weight‐kg (W), length‐cm (L), head circumferences‐cm (HC), skinfold thicknesses mm [triceps (TRI), thigh (THI), subscapular (SCP), and iliac (IL)], and FM by PEA POD® and Infant‐QMR were collected. Stepwise linear regression determined the model that best predicted FM. Results: Weight, length, head circumference, and skinfolds of triceps, thigh, and subscapular, but not iliac, significantly predicted FM throughout infancy in both the Infant‐QMR and PEA POD models. Sex had an interaction effect at 3 days and 15 weeks for both the models. The coefficient of determination [R 2 ] and root mean square error were 0.87 (66 g) at 3 days, 0.92 (153 g) at 15 weeks, and 0.82 (278 g) at 54 weeks for the Infant‐QMR models; 0.77 (80 g) at 3 days and 0.82 (195 g) at 15 weeks for the PEA POD models respectively. Conclusions: Both PEA POD and Infant‐QMR derived models predict FM using skinfolds, weight, head circumference, and length with acceptable R 2 and residual patterns.